Circular RNAs as Potential Theranostics in the Cardiovascular System - Yihua Bei; Tingting Yang; Lijun Wang; Paul Holvoet; Saumya Das; Joost P.G. Sluijter; Marta Chagas Monteiro; Yang Liu; Qiulian Zhou; Junjie Xiao (Elsevier, 2018)
Cardiovascular diseases (CVDs) represent the largest contributor to mortality worldwide. Identification of novel therapeutic targets and biomarkers for CVDs is urgently needed. Circular RNAs (circRNAs) are endogenous, abundant, and stable non-coding RNAs formed by back-splicing events. Their role as regulators of gene expression has been increasingly reported. Notably, circRNAs mediate essential physiological and pathological processes in the cardiovascular system. Our first aim, therefore, is to summarize recent advances in the role of circRNAs in cardiac development as well as in pathogenesis of various CVDs. Because circRNAs are stable in circulation and their dynamic changes may reflect different disease stages, they are considered ideal biomarkers. Therefore, our second aim is to review studies that have identified circulating circRNAs as biomarkers for CVDs. Finally, we discuss the shortage of functional studies and the limitations of available clinical studies and provide future perspectives. Keywords: cardiovascular disease, circular RNA, myocardial infarction, heart failure, cardiomyopathy, atherosclerosis, fibrosis, endothelial dysfunction, therapeutic targets, biomarkers